Angiotensin-Converting Enzyme in Smooth Muscle Cells Promotes Atherosclerosis—Brief Report. Issue 6 (June 2016) - Chen, Xiaofeng; Howatt, Deborah A.; Balakrishnan, Anju; Moorleghen, Jessica J.; Wu, Congqing; Cassis, Lisa A.; Daugherty, Alan; Lu, Hong
Abstract : Objective—: Angiotensin-converting enzyme (ACE) is present in many cell types of atherosclerotic lesions. This study determined whether ACE activity in endothelial and smooth muscle cells (SMCs), 2 major resident cell types of the aorta, contributes to hypercholesterolemia-induced atherosclerosis. Approach and Results—: All study mice were in low-density lipoprotein receptor −/− background. To determine the contribution of ACE on endothelial cells to atherosclerosis, female ACE floxed mice were bred to male Tie2-Cre transgenic mice. Endothelial cell–specific deletion of ACE significantly decreased serum ACE activity, but had no effect on systolic blood pressure and atherosclerosis. Because ACE protein is present on SMCs, the most abundant cell type of the aorta, we then determined whether ACE on SMCs contributes to atherosclerosis. ACE was depleted from SMCs by breeding female ACE floxed mice with male SM22-Cre transgenic mice. SMC-specific deficiency of ACE did not affect ACE activity in serum, but ablated its presence and activity in the aortic media. Although SMC-specific deficiency of ACE had no effect on systolic blood pressure, it significantly attenuated hypercholesterolemia-induced atherosclerosis in both male and female mice. Conclusions—: These studies provide direct evidence that ACE derived from endothelial cells does not play a critical role in atherosclerosis. Rather, SMC-derived ACE contributes to atherosclerosis, independent of circulating ACE activity and blood pressure. Abstract : Supplemental Digital Content is available in the text.